Association of mothers’ single nucleotide polymorphism of Vitamin D receptor’s FokⅠ gene with risk of preterm birth and birth weight: a review - Habiba, Umme (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.